Kinetic modeling of microbial growth, enzyme activity, and gene deletions: An integrated model of β‐glucosidase function in Cellvibrio japonicus. Issue 12 (4th September 2020) - Hwang, Jeanice; Hari, Archana; Cheng, Raymond; Gardner, Jeffrey G.; Lobo, Daniel
Abstract: Understanding the complex growth and metabolic dynamics in microorganisms requires advanced kinetic models containing both metabolic reactions and enzymatic regulation to predict phenotypic behaviors under different conditions and perturbations. Most current kinetic models lack gene expression dynamics and are separately calibrated to distinct media, which consequently makes them unable to account for genetic perturbations or multiple substrates. This challenge limits our ability to gain a comprehensive understanding of microbial processes towards advanced metabolic optimizations that are desired for many biotechnology applications. Here, we present an integrated computational and experimental approach for the development and optimization of mechanistic kinetic models for microbial growth and metabolic and enzymatic dynamics. Our approach integrates growth dynamics, gene expression, protein secretion, and gene‐deletion phenotypes. We applied this methodology to build a dynamic model of the growth kinetics in batch culture of the bacterium Cellvibrio japonicus grown using either cellobiose or glucose media. The model parameters were inferred from an experimental data set using an evolutionary computation method. The resulting model was able to explain the growth dynamics of C. japonicus using either cellobiose or glucose media and was also able to accurately predict the metabolite concentrations in the wild‐type strain as well as in β‐glucosidase gene deletion mutant strains. We validated the model by correctly predicting the non‐diauxic growth and metabolite consumptions of the wild‐type strain in a mixed medium containing both cellobiose and glucose, made further predictions of mutant strains growth phenotypes when using cellobiose and glucose media, and demonstrated the utility of the model for designing industrially‐useful strains. Importantly, the model is able to explain the role of the different β‐glucosidases and their behavior under genetic perturbations. This integrated approach can be extended to other metabolic pathways to produce mechanistic models for the comprehensive understanding of enzymatic functions in multiple substrates. Abstract : An integrated computational and experimental approach is presented for the development and optimization of mechanistic models for microbial growth and metabolic and enzymatic dynamics. A growth kinetic model of the bacterium Cellvibrio japonicus was built to explain the dynamics and metabolite concentrations in the wild‐type and β‐glucosidase mutant strains grown in batch culture in cellobiose, glucose, or mixed media. This integrated approach can be used towards the comprehensive understanding of enzymatic functions in multiple substrates and for designing industrially‐useful strains.